The Effect of Health Promotion Through Audio Visual Media About HIV AIDS On Housewives Knowledge - Dhita Kris Prasetyanti; Anis Nikmatul Nikmah; Kania Tantriyani (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Human Immunodeficiency Syndrome is a virus that attacks the human immune system, while Acquired Immunodeficiency Syndrome (AIDS) is an immune syndrome caused by HIV infection. Housewives are more susceptible to exposure to the HIV virus due to sexual behavior of their partners. The purpose of this study was to determine the effectiveness of health promotion through audio-visual media, about HIV / AIDS on housewives' knowledge. This research is a pre experiment. The population in this study was all housewives. The sample size of 16 respondents was taken based on purposive sampling. Statistical test using Wilcoxon. Based on the Wilcoxon test, the p-value was 0,000, so that there was an effect of providing health promotion about HIV AIDS using audio-visual media on housewives' knowledge about HIV AIDS. It is hoped that housewives can increase their knowledge in preventing HIV AIDS so that the incidence of HIV AIDS can be prevented early